Filmes finos supercondutores sob um campo magnético inomogêneo: diminuição da profundidade da frente de fluxo magnético - Araújo, Ítalo Moreira de (2021)
The phenomenon of superconductivity was discovered by scientist Heike Kamerlingh Onnes in 1911, while studying the resistivity of mercury when cooled below 4,2 K. As predicted by Alexei Abrikosov in 1957, materials from a class of superconductors - currently labeled as Type II - when in the presence of a magnetic field, do admit the entry of flux, in the form of vortices, even being in the superconducting state. A relevant problem for the application of superconductors is the movement of these vortices in the material, which generates dissipation and leads to a local increase in temperature, making the superconducting state less robust. One of the strategies used to avoid this unwanted effect, which results from the viscous movement of vortices, is the artificial inclusion of pinning centers, which act as potential wells for the vortices, making it difficult for them to move. Recently, a considerable number of studies have been directed to the so-called conformal arrangements, which are characterized by the maintenance of the hexagonal symmetry of the original vortex lattice and the introduction of a gradient in the spatial distribution of pinning centers, in the form of arcs, promoting a local increase in the critical current, especially in regimes of high fields and temperatures. In a recent study, performed using computer simulations carried out based on the Ginzburg-Landau theory, it was shown that through combinations of homogeneous and inhomogeneous magnetic fields, it is possible to produce a conformal arrangement of vortices even in a specimen without artificial inclusions. It was precisely this study that inspired the work described here. Thus, with the use of the magneto-optic imaging technique based on the Faraday Effect, the distribution of magnetic flux and the penetration depth of the flux front in the superconducting phase of the studied device was mapped. It consists of a square film of Nb, surrounded by a loop, also square, of Nb. The device was lithographed from a 200 nm thick Nb film. In all cases treated here, the applied field was always perpendicular to the plane of the device. The field profile generated by the superconducting loop was obtained by direct calculation, using the Biot-Savart Law. The superconducting ring was properly characterized, both with respect to the applied current and the applied field at a fixed temperature, in order to guarantee conditions for the device - i.e., the ring and the film inside it - to remain in the superconducting state along the experiments. We thus performed a series of comparisons of the penetration depth of the magnetic flux front using magneto-optic images, always maintaining an equal effective field condition. We used two sample cooling routines: one with field (FC, field cooling), which could be either homogeneous or inhomogeneous, and another in the absence of field (ZFC, zero field cooling). In addition, we also varied the sense of the FC field, always keeping in the same (positive) direction the homogeneous field that was applied during the experiments. The results showed a hierarchy in the penetration depth: the most profound was the negative inhomogeneous field condition, that is, the one in which antivortices were trapped in the superconductor during cooling. A significantly deeper penetration was presented for the condition of FC in a negative homogeneous field; in the sequence, the ZFC condition appears and then there is the positive homogeneous FC condition. The configuration with the lowest flux penetration depth was the one with inhomogeneous field in the same direction as the applied field. Therefore, the interactions between the vortices nucleated by the increase in the applied field and the vortices or antivortices trapped during the cooling of the film proved to be important in favor of vortex-vortex repulsion. In addition, among the five different cooling situations which we have studied, the inhomogeneous field condition is one in which the system exhibits the greater effective shielding capacity.